Age-related changes in peripheral nociceptor function. (15th September 2022) - Jennings, Elaine M.; Sullivan, Laura C.; Jamshidi, Raehannah J.; LoCoco, Peter M.; Smith, Hudson R.; Chavera, Teresa S.; Berg, Kelly A.; Clarke, William P.
Abstract: Pain and pain management in the elderly population is a significant social and medical problem. Pain sensation is a complex phenomenon that typically involves activation of peripheral pain-sensing neurons (nociceptors) which send signals to the spinal cord and brain that are interpreted as pain, an unpleasant sensory experience. In this work, young (4–5 months) and aged (26–27 months) Fischer 344 x Brown Norway (F344xBN) rats were examined for nociceptor sensitivity to activation by thermal (cold and heat) and mechanical stimulation following treatment with inflammatory mediators and activators of transient receptor potential (TRP) channels. Unlike other senses that decrease in sensitivity with age, sensitivity of hindpaw nociceptors to thermal and mechanical stimulation was not different between young and aged F344xBN rats. Intraplantar injection of bradykinin (BK) produced greater thermal and mechanical allodynia in aged versus young rats, whereas only mechanical allodynia was greater in aged rats following injection of prostaglandin E2 (PGE2 ). Intraplantar injection of TRP channel activators, capsaicin (TRPV1), mustard oil (TRPA1) and menthol (TRPM8) each resulted in greater mechanical allodynia in aged versus young rats and capsaicin-induced heat allodynia was also greater in aged rats. A treatment-induced allodynia that was greater in young rats was never observed. The anti-allodynic effects of intraplantar injection of kappa and delta opioid receptor agonists, salvinorin-A and D-Pen 2, D-Pen 5 ]enkephalin (DPDPE), respectively, were greater in aged than young rats, whereas mu opioid receptor agonists, [D-Ala2, N-MePhe4, Gly-ol]-enkephalin (DAMGO) and morphine, were not effective in aged rats. Consistent with these observations, in primary cultures of peripheral sensory neurons, inhibition of cAMP signaling in response to delta and kappa receptor agonists was greater in cultures derived from aged rats. By contrast, mu receptor agonists did not inhibit cAMP signaling in aged rats. Thus, age-related changes in nociceptors generally favor increased pain signaling in aged versus young rats, suggesting that changes in nociceptor sensitivity may play a role in the increased incidence of pain in the elderly population. These results also suggest that development of peripherally-restricted kappa or delta opioid receptor agonists may provide safer and effective pain relief for the elderly. Highlights: Nociceptor sensitivity to thermal and mechanical stimulation did not differ between young and aged F344xBNrats. Inflammatory mediators and TRP channel activators produced greater thermal and mechanical allodynia in aged rats. Intraplantar injection of kappa and delta opioid receptor agonists produced greater anti-allodynic response in aged rats. whereas mu opioid receptor agonists, DAMGO and morphine, were not effective in aged animals. In primary cultures of peripheral sensory neurons, inhibition of cAMP signaling in response to delta and kappa opioid receptor agonists was greater in cultures derived from aged rats. By contrast, mu receptor agonists did not inhibit cAMP signaling in cultures from aged rats. Age-related changes in nociceptors generally favor increased pain signaling in aged rats, suggesting that changes in nociceptor sensitivity may play a major role in the increased incidence of pain in the elderly population.